Emissions of trace elements during the 2012–2013 effusive eruption of Tolbachik volcano, Kamchatka: enrichment factors, partition coefficients and aerosol contribution - Zelenski M.; Malik N.; Taran Yu. (Journal of Volcanology and Geothermal Research, 2014)
Abstract Gases and aerosols from the 2012–13 effusive eruption of Tolbachik basaltic volcano, Kamchatka, were sampled in February and May, 2013, from a lava tube window located 300 m from the eruptive crater; temperature at the sampling point was 1060–1070 °C. The chemical and isotopic compositions of the sampled gases (92.4 H2O, 3.5 CO2, 2.3 SO2 on average; δD from − 25.0 to − 38.6‰) correspond to a typical volcanic arc gas without dilution by meteoric or hydrothermal water. Halogen contents in the gases (1.37 HCl, 0.5 HF) were higher than average arc values. The total amount of analyzed metallic and metalloid (trace) elements in the gas exceeded 665 ppm. Six most abundant trace elements, K (250 ppm), Na (220 ppm), Si (74 ppm), Br (48 ppm), Cu (21 ppm) and Fe (12 ppm), accounted for 95 of the total content of trace elements in the gas. The gases contained 24 ppb Re, 12 ppb Ag, 4.9 ppb Au and 0.45 ppb Pt. Refractory rock-forming elements (Mg, Al, Ca) and some other elements such as Ba and Th were transported mainly in the form of silicate microspheres and altered rock particles. The concentrations of metals in the eruptive Tolbachik gases are higher than the corresponding concentrations in high-temperature fumaroles worldwide, although the mutual ratios of the elements are approximately the same. The gas/magma partition coefficients of eleven elements exceed unity, including the non-metals F, S, Cl, Br, As, Se and Te and the rare metals Cd, Re, Tl and Bi. Despite the relatively low concentrations of trace elements in the volcanic gases at the highest temperatures, superficial magma degassing provides information on the sources and sinks of metals.